Host galaxy properties of radio selected AGN. Issue Volume 9:Issue S304(2013) (25th July 2014) - Bonzini, M.; Mainieri, V.; Padovani, P.; Kellermann, K. I.; Miller, N.; Rosati, P.; Tozzi, P.; Vattakunnel, S.
Abstract: With the goal of investigating the link between black hole (BH) and star formation (SF) activity, we study a deep sample of radio selected star forming galaxies (SFGs) and active galactic nuclei (AGNs). Using a multi-wavelength approach we characterize their host galaxies properties (stellar masses, optical colors, and morphology). Moreover, comparing the star formation rate derived from the radio and far-infrared luminosity, we found evidences that the main contribution to the radio emission in the radio-quiet AGNs is star-formation activity in their host galaxy.